2012
DOI: 10.1111/j.1445-2197.2012.06247.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent laryngeal nerve injury in thyroid surgery: a review

Abstract: Recurrent laryngeal nerve palsy (RLNP) is an important and potentially catastrophic complication of thyroid surgery. Permanent RLNP occurs in 0.3-3% of cases, with transient palsies in 5-8%. A literature review and analysis of recent data regarding RLNP in thyroid surgery was performed, with particular focus on the identification of high-risk patients, the role of intraoperative identification and dissection of the nerve, and the role of intraoperative neuromonitoring (IONM) and optimal perioperative nerve ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
0
22

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(164 citation statements)
references
References 66 publications
(135 reference statements)
5
137
0
22
Order By: Relevance
“…surgery has a high incidence of complications such as recurrent laryngeal nerve injury, hypoparathyroidism, and hypothyroidism 3,4,29,30 ; however, the complication rate reported for RFA was low in the study by Baek et al, 25 a 3.3% complication rate with thyroid RFA in their multicenter study. In our current study, the RFA complication rate was found to be lower than that of surgery.…”
Section: Figurementioning
confidence: 66%
“…surgery has a high incidence of complications such as recurrent laryngeal nerve injury, hypoparathyroidism, and hypothyroidism 3,4,29,30 ; however, the complication rate reported for RFA was low in the study by Baek et al, 25 a 3.3% complication rate with thyroid RFA in their multicenter study. In our current study, the RFA complication rate was found to be lower than that of surgery.…”
Section: Figurementioning
confidence: 66%
“…5 Review of literature revealed that the prevalence of RLN palsy varies from centre to centre depending upon the level of experience in thyroid surgery and the nature of surgery. Aytec and colleagues 15 reported 3.5% and 1.2% incidence of transient and permanent RLN injury, respectively and Hayward et al, 7 reported that permanent RLNP occurs in 0.3-3% of cases, with transient palsies in 5-8%, Chaing 14 has reported figures of 5.1% and 0.9% for transient and permanent RLN injury. Xu and colleagues 16 have reported 0.2% incidence of permanent RLN injury in their study in China.…”
Section: Results and Observationsmentioning
confidence: 99%
“…6 An almost certain way to ensure the integrity of the RLN is to always identify the nerve during all surgical procedure on thyroid and parathyroid glands. 7 Anatomy of laryngeal nerve is shown in Figure 1. …”
Section: Introductionmentioning
confidence: 99%
“…Whereas thyroid surgery is widely available and safe in many centers, it still carries a 2-10 % risk of complications, such as neck scarring, hypothyroidism, postoperative hypoparathyroidism, recurrent laryngeal nerve injury, and the risks associated with general anesthesia. Surgery is also expensive, and may not be appropriate for a surgically high-risk individual [10,[25][26][27][28][29][30]. Over the last decade, thermal ablation techniques, such as laser ablation (LA), radiofrequency ablation (RFA), high-intensity-focus ultrasound (HIFU), and microwave ablation (MWA), have been proposed for the treatment of benign solid thyroid nodules, with encouraging results.…”
Section: Introductionmentioning
confidence: 99%